A Model of Inherited Wealth - Blinder, Alan S. (Quarterly Journal of Economics, 1973)
I. Introduction, 608. — II. Elements of a model of inheritance, 610. — III. Primogeniture, 612. — IV. The mating function, 614. — V. Random mating, 616. — VI. Class mating, 620. — VII. Assortative mating, 623. Every generation regards as natural the institutions to which it is accustomed. — R. H. Tawney